Intrinsic functional and structural connectivity of emotion regulation networks in obsessive‐compulsive disorder. Issue 2 (25th September 2018) - Picó‐Pérez, Maria; Ipser, Jonathan; Taylor, Paul; Alonso, Pino; López‐Solà, Clara; Real, Eva; Segalàs, Cinto; Roos, Annerine; Menchón, José M.; Stein, Dan J.; Soriano‐Mas, Carles
Abstract: Despite emotion regulation being altered in patients with obsessive‐compulsive disorder (OCD), no studies have investigated its relation to multimodal amygdala connectivity. We compared corticolimbic functional and structural connectivity between OCD patients and healthy controls (HCs), and correlated this with the dispositional use of emotion regulation strategies and with OCD severity. OCD patients ( n = 73) and HCs ( n = 42) were assessed for suppression and reappraisal strategies using the Emotion Regulation Questionnaire (ERQ) and for OCD severity using the Yale‐Brown Obsessive‐Compulsive Scale. Resting‐state functional magnetic resonance imaging (rs‐fMRI) connectivity maps were generated using subject‐specific left amygdala (LA) and right amygdala (RA) masks. We identified between‐group differences in amygdala whole‐brain connectivity, and evaluated the moderating effect of ERQ strategies. Significant regions and amygdala seeds were used as targets in probabilistic tractography analysis. Patients scored higher in suppression and lower in reappraisal. We observed higher rs‐fMRI RA–right postcentral gyrus (PCG) connectivity in HC, and in patients this was correlated with symptom severity. Reappraisal scores were associated with higher negative LA–left insula connectivity in HC, and suppression scores were negatively associated with LA–precuneus and angular gyri connectivity in OCD. Structurally, patients showed higher mean diffusivity in tracts connecting the amygdala with the other targets. RA–PCG connectivity is diminished in patients, while disrupted emotion regulation is related to altered amygdala connectivity with the insula and posterior brain regions. Our results are the first showing, from a multimodal perspective, the association between amygdala connectivity and specific emotional processing domains, emphasizing the importance of amygdala connectivity in OCD pathophysiology.